The relationship between internalizing and externalizing symptoms and cultural resilience factors in indigenous Sami youth from Arctic Norway - Bals, Margrethe; Turi, Anne Lene; Skre, Ingunn; Kvernmo, Siv (International Association of Circumpolar Health Publishers, 2011)
This is the accepted manuscript version of the article. Published version in International Journal of Circumpolar Health is available in Munin at http://hdl.handle.net/10037/3997 This article is part of Margrethe Bals' doctoral thesis, which is available in Munin at http://hdl.handle.net/10037/2934 Objectives. To examine whether enculturation factors, like cultural activities, ethnic pride, and native language competence, are related to decreasing internalizing and externalizing symptoms in indigenous Sami youth from Arctic Norway. The impact of self-efficacy on the relationship between enculturation factors and mental health problems was also examined. Study design. Population-based, cross-sectional questionnaire study. Methods. The Norwegian Arctic Adolescent Health Study was conducted among 10th graders in junior high schools in North Norway during 2003-2005. The study sample consisted of 450 indigenous Sami youth, aged 15-16 years. Internalizing symptoms were measured with the Hopkins Symptom Check List-10 (HSCL-10), while externalizing symptoms were measured by two subscales of the Strengths and Difficulties Questionnaire (SDQ). Results. For boys, participating in cultural activities and self-efficacy were associated with decreasing internalizing symptoms. Additionally, self-efficacy interacted with Sami language competence and cultural activities: when self-efficacy increased, these enculturation factors were related to symptom reduction. For girls, self-efficacy had an independent effect on internalizing symptoms and self-efficacy also strengthened the relationship between participation in cultural activities and reduced externalizing symptoms. Sami language competence was related to reduction of both internalizing and externalizing symptoms in girls. Conclusions. In the present study, several enculturation factors and self-efficacy were identified as potential protective factors against mental health problems. In order to develop theoretical models that explain the mechanisms between cultural ...